2004
DOI: 10.1111/j.1464-410x.2004.05017.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of neurokinin A‐ and substance P‐induced contractions in rat detrusor smooth muscle in vitro

Abstract: (1 m mol/L), peptidase inhibitors (captopril, thiorphan and bestatin; 1 m mol/L each) or piroxicam (10 m mol/L). The rank order of potency of agonists was neurokinin A > substance P > carbachol. Contractile responses to neurokinin A and substance P, like the contractile responses to carbachol, were abolished in a nominally Ca 2+-free medium and significantly reduced by nifedipine (1 m mol/L). SKF-96365 (60 m mol/L), an inhibitor of receptor-mediated Ca 2+ entry, abolished the nifedipine-resistant response to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 33 publications
2
9
1
1
Order By: Relevance
“…However, the receptors that it activates are more widely distributed and they are expressed on smooth muscle as well as on afferent terminals [22,23]. Substance P significantly increased both ATP and NO release from intact strips.…”
Section: Discussionmentioning
confidence: 99%
“…However, the receptors that it activates are more widely distributed and they are expressed on smooth muscle as well as on afferent terminals [22,23]. Substance P significantly increased both ATP and NO release from intact strips.…”
Section: Discussionmentioning
confidence: 99%
“…In human tissue, receptor density seems slightly higher in the colon compared to the bladder (Burcher et al 2000; Warner et al 2003). In vitro contractility studies in several species (human, rat, hamster) demonstrated NK 2 receptor mediated contraction of the bladder (Giuliani et al 1993; Palea et al 1996; Quinn et al 2004; Tramontana et al 1998; Warner et al 2003) and gastrointestinal tract (Carini et al 2001; Lecci et al 2006; Lecci et al 2004; Mule et al 2000). Moreover, the NK 2 receptor mediated bladder contractions in human SCI-induced neurogenic overactive detrusor strips were similar to those from detrusor tissue taken from normal individuals (Sellers et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To determine the involvement of extracellular Ca 2+ in stretch‐induced MYPT1 phosphorylation, strips were placed in a Ca 2+ ‐free Krebs solution containing 1 mM EGTA to chelate extracellular calcium. Strips were maintained in the Ca 2+ ‐free solution for 30 min, during which time the bath solution was changed three times before stretching of the detrusor strips 15. Stretched strips with or without Y‐27632 incubation and non‐stretched strips were removed from the organ bath and processed as described above.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the possible contribution of Ca 2+ released from intracellular stores to stretch‐induced MYPT1 phosphorylation, strips were incubated with 1 µM thapsigargin,16 a potent inhibitor of the sarcoplasmic Ca 2+ ATP‐ase pump, in Ca 2+ ‐free Krebs solution for 30 min. The concentration of thapsigargin was based on a previous study 15. MYPT1 phosphorylation was determined as described above.…”
Section: Methodsmentioning
confidence: 99%